Advances in functional guest materials for resistive gas sensors. Issue 38 (30th August 2022) - Wang, Ze; Zhu, Lei; Wang, Jingzhao; Zhuang, Rui; Mu, Pengfei; Wang, Jianan; Yan, Wei
Abstract : The introduction of functional guest materials is an effective way to improve the sensing performance of resistive gas sensors. Abstract : Resistive gas sensors are considered promising candidates for gas detection, benefiting from their small size, ease of fabrication and operation convenience. The development history, performance index, device type and common host materials (metal oxide semiconductors, conductive polymers, carbon-based materials and transition metal dichalcogenides) of resistive gas sensors are firstly reviewed. This review systematically summarizes the functions, functional mechanisms, features and applications of seven kinds of guest materials (noble metals, metal heteroatoms, metal oxides, metal–organic frameworks, transition metal dichalcogenides, polymers, and multiple guest materials) used for the modification and optimization of the host materials. The introduction of guest materials enables synergistic effects and complementary advantages, introduces catalytic sites, constructs heterojunctions, promotes charge transfer, improves carrier transport, or introduces protective/sieving/enrichment layers, thereby effectively improving the sensitivity, selectivity and stability of the gas sensors. The perspectives and challenges regarding the host–guest hybrid materials-based gas sensors are also discussed.